Obesity and Breast Cancer: A Paradoxical and Controversial Relationship Influenced by Menopausal Status - García-Estévez, Laura; Cortés, Javier; Pérez, Silvia; Calvo, Isabel; Gallegos, Isabel; Moreno-Bueno, Gema (Frontiers in Oncology, 2021)
Breast cancer is the most common tumor in women worldwide, and an increasing public health concern. Knowledge of both protective and negative risk factors is essential for a better understanding of this heterogenous disease. We undertook a review of the recent literature and evaluated the relationship between obesity mediators and breast cancer development depending on menopausal status. Excess weight is now pandemic and has replaced tobacco as the main lifestyle-related risk factor for premature death. Although the prevalence of obesity/overweight has increased globally over the last 50 years, the potential harm attributable to excess fat has generally been underestimated. The relationship between overweight/obesity, breast cancer and overall risk appears to be highly dependent on menopausal status. Thus, obesity increases the risk of breast cancer in women postmenopause but, conversely, it appears to be protective premenopause. We evaluate the role of different clinical factors potentially involved in this seemingly contradictory relationship, including estrogen, mammogram density, adipokines, insulin-signaling pathway activation, and inflammatory status. A key focus of this review is to better understand the impact of body mass index and menopausal status on these clinical factors and, hence, provide some clarity into the inter-relationships involved in this controversial issue.